Analysis Of Willingness To Pay (WTP) To Improve The Services Of Pdam Tirta Lamaindo In Bahari Village, Sampolawa District, South Buton Regency - Nur Gaya; La Ode Midi; Surya Cipta Ramadhan Kete; Muhammad Saleh Qadri (International journal of technology and education research, 2025)
The purpose of this study was to determine the willingness to pay of the community towards PDAM Tirta Lamaindo and to identify the factors that influence willingness to pay or WTP in Bahari Village, Sampolawa District, South Buton Regency. This study was conducted in April–May 2025 with a sample size of 67 households determined using the Slovin formula and purposive sampling technique. Data were collected through questionnaires, observations, interviews, literature studies, and documentation. The types of data used included quantitative and qualitative data, with primary and secondary data sources. Data analysis was performed using the Contingent Valuation Method (CVM) to calculate the WTP value and multiple linear regression analysis to determine the factors affecting WTP with the help of SPSS 25 software. The results showed that the average WTP of the community was IDR 23,283.58 per month per household, with the majority of respondents willing to pay IDR 20,000. Factors influencing WTP included user age, income, highest level of education, number of users, water quality, and monthly water payments. Income influenced the amount of WTP, with higher income leading to greater willingness to pay. Conversely, higher education and current monthly water payments tend to decrease WTP. Age, number of water users in the household, and physical water quality do not significantly affect WTP. These findings indicate that the economic aspects of the community are an important consideration in efforts to improve service quality and adjust clean water tariffs.